(NaNNA kARENINA(B: [(NrOMAN(B] / s (N~ASTX (B2s - (NtOLSTOJ(B, (NlEW nIKOLAEWI^s ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1987)
(NwTORAQ POLOWINA ROMANA(B.s
rus
Keywords: (NpSIHOLOGI^ESKIJ ROMANs; (NsOCIALXNYJ ROMANs